2013
DOI: 10.1103/physrevb.88.045419
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic behavior of the transmission phase through confined correlated electronic systems

Abstract: We investigate the effect of electronic correlations on the transmission phase of quantum coherent scatterers, considering quantum dots in the Coulomb blockade regime connected to two singlechannel leads. We focus on transmission zeros and the associated π-phase lapses that have been observed in interferometric experiments. We numerically explore two types of models for quantum dots: (i) lattice models with up to eight sites, and (ii) resonant level models with up to six levels. We identify different regimes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
(140 reference statements)
0
15
0
Order By: Relevance
“…The observed phase locking has posed a theoretical puzzle since it appears to contradict the expectation that eigenstates of different resonances are uncorrelated. Numerous theoretical papers have addressed the emergence of universal behavior in large QDs [1][2][3][7][8][9][10][11][12][13][14][15][16][17]. Some works have pointed to the importance of electronic correlations in establishing universal behavior [15], while detailed many-body numerical calculations recently disputed such a view [17].…”
Section: Introductionmentioning
confidence: 99%
“…The observed phase locking has posed a theoretical puzzle since it appears to contradict the expectation that eigenstates of different resonances are uncorrelated. Numerous theoretical papers have addressed the emergence of universal behavior in large QDs [1][2][3][7][8][9][10][11][12][13][14][15][16][17]. Some works have pointed to the importance of electronic correlations in establishing universal behavior [15], while detailed many-body numerical calculations recently disputed such a view [17].…”
Section: Introductionmentioning
confidence: 99%
“…Switching to the problem of the phase evolution between the n th and (n + 1) st CB peaks, we distinguish the case where the transmission amplitude at intermediate energies is dominated by the contributions arising from these two resonances, from that with large fluctuations of the level width among different levels, where far-away resonances might characterize the intermediate behavior. The first scenario supposes the absence of strong fluctuations of the level-widths, and has been termed [27] restricted off-resonance (ROR) behavior. The second scenario of large PWA fluctuations, termed unrestricted off-resonance (UOR) behavior, is expected (and numerically verified [27,28]) to be rare.…”
Section: Transmission Phase and Peak-heights In The Coulomb Blockmentioning
confidence: 99%
“…The first scenario supposes the absence of strong fluctuations of the level-widths, and has been termed [27] restricted off-resonance (ROR) behavior. The second scenario of large PWA fluctuations, termed unrestricted off-resonance (UOR) behavior, is expected (and numerically verified [27,28]) to be rare.…”
Section: Transmission Phase and Peak-heights In The Coulomb Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in that direction was obtained studying the statistical properties of the parity correlations between succesive wave functions in ballistic chaotic quantum dots [13]. Another interesting path followed for the analysis of the experimental results is a many-body extension of the constant-interaction model (CIM) for the description of resonances in quantum dots [14,15,16]. In the regime where the distance between resonances is much smaller than the width of the resonant levels Karrasch et al found that the number of phase lapses could be increased by moderate interactions.…”
Section: Introductionmentioning
confidence: 99%